2011
DOI: 10.1007/s00134-011-2222-4
|View full text |Cite
|
Sign up to set email alerts
|

Early and late outcome after single step dilatational tracheostomy versus the guide wire dilating forceps technique: a prospective randomized clinical trial

Abstract: PurposePercutaneous tracheostomy is frequently performed in long-term ventilated patients in the intensive care unit (ICU). Unfortunately, despite many years of experience, the optimal technique is still unknown, especially considering the occurrence of late complications. The purpose of this study was to determine which of the two most frequently used percutaneous tracheostomy techniques performs best with the emphasis on late complications.MethodsThis prospective randomized trial involved 120 patients, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 23 publications
3
37
1
2
Order By: Relevance
“…The median procedure length was shorter in the US group, with the length of bronchoscopy-guided PDT being similar to that of previous [14][15][16][17][18][19][20][21][22][23] 13 [10][11][12][13][14][15][16][17][18][19][20][21][22] .004…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The median procedure length was shorter in the US group, with the length of bronchoscopy-guided PDT being similar to that of previous [14][15][16][17][18][19][20][21][22][23] 13 [10][11][12][13][14][15][16][17][18][19][20][21][22] .004…”
Section: Discussionsupporting
confidence: 82%
“…Guinot et al [13] observed an overall complication rate of 33% in a population of 50 obese and nonobese patients submitted to US-guided tracheostomy, with bleeding accounting for 6%, surgical site infection for 2%, desaturation for 6%, and hypotension for 6%. In a trial of 120 patients submitted to bronchoscopy-guided PDT, 15% of patients had minor blood loss, 2.5% had transient hypoxemia, and 15% had the endotracheal tube punctured [18]. In the 2 largest retrospective cohorts previously published on the topic, including a total of 4162 patients in the analyses, the major complication rates were very low, ranging from 0.38% to 1.4% [2,19].…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies show rates of 1% for major complications and highly variable rates (up to 60%) of minor complications in PDT [14,15]. Our series resulted in a comparable rate (0.35%) of major complications, including one life-threating vascular injury.…”
Section: Discussionsupporting
confidence: 73%
“…33 Several randomized, longitudinal trials comparing the single dilation Ciaglia technique and the Griggs technique have also been conducted. [34][35][36][37][38] A meta-analysis of these trials found evidence of superiority of the Ciaglia technique using a combined endpoint representing procedural difficulties and bleeding. 39 The Role of Cricothyrotomy, Tracheostomy…”
Section: The Griggs Techniquementioning
confidence: 99%